Minimum Quality Standards and Predatory Behaviour - Luca Lambertini; Carlo Scarpa (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1999)
This paper shows that the introduction of a premium quality standard can have repercussions on the market structure, opening the possibility of predatory behavior. The predatory equilibrium exists independently of whether or not adjustment costs are present. Moreover, whenever predation is an equilibrium, it is selected by the risk dominance criteria.
Keywords: 330